Obesity - lifestyle choice or a disease? Changes in perception of obesity - Pawlikowska-Gorzelańczyk, Anna; Szuster, Ewa; Kostrzewska, Paulina; Mandera-Grygierzec, Amanda (Journal of Education, Health and Sport, 2022)
Introduction and purpose Nowadays obesity has become a main problem in the world’s population and it is beginning to replace undernutrition and infectious diseases. Over the years perception of obesity has diametrically changed. Obesity is no longer the result of bad choices but serious medical problem. The aim of this study is to show how changes in perception of obesity affect the obesity pandemic. Review methods The literature review included articles available on the websites of health-related organizations and databasis on PubMed. As a part of analysis systematic search of current scientific data was performed. Description of the state of knowledge Obesity is defined as an abnormal or excessive fat accumulation and in adults BMI ≥30 is necessary to recognize it. Obesity has plenty of consequences such as diabetes, hypertension, cancers etc. In June 2013 the American Medical Association made a decision to recognize obesity as a disease. That changed the perception of obesity by the public and caused many actions in prevention and treatment. Management of obese patient consists of diagnosis the obesity-causing diseases, recognition of eating and physicall activity habits. Surgical as well pharmacological treatment is available and should be individually considered. Summary Recognition of obesity as a disease requires health organisations to build special prevention and treatment programs. Nowadays there is an array of treatment methods for obesity. However the most important method to stop the pandemic is education and promotion of a healthy lifestyle, according to the motto, prevention is better than cure.